Ethiopia country brief - Warren, Andrea (Transform Nutrition, 2016)
The ‘Stories of Change in Nutrition’ research project aims to generate experiential learning for countries with high burdens of malnutrition to start to fill gaps in our understanding of how policies to address nutrition are made and how these policies play out in implementation in particular contexts. This brief focuses on three overlapping ‘Stories of Change’: We first discuss the evolution of Ethiopia’s nutrition sensitive agendas within the agriculture, social protection, and health sectors over the past decade. The second story details the ongoing alignment of national nutrition agendas with the capacities to implement them at zone and woreda levels. The third story centres on the challenges communities face in engaging with nutrition programming in a changing, but increasingly limiting, environment. The objective of this brief is to draw attention to the real world challenges of implementing nutrition sensitive agendas and provide recommendations for how to move forward with nutrition sensitive programming.